PENGALAMAN MEMBANGUN RELASI VIRTUAL DI MEDSOS: STUDI TENTANG IBU RUMAH TANGGA MENGEMBANGKAN USAHA DI MEDSOS - Sellametha Alika Permata Gunaeri (Jurnal Sosiologi UPR, 2025)
This study aims to explore the role of social media in enabling housewives to start and develop online businesses, focusing on strategies for building virtual relationships. The research employs a qualitative approach with a case study design involving several successful housewives running businesses through social media. The findings indicate that social media offers flexibility, allowing housewives to manage businesses without neglecting domestic responsibilities. Strategies such as consistent content creation, personalized interactions, and participation in online communities are effective in building strong virtual relationships, boosting sales, and fostering customer loyalty. However, challenges such as limited time, capital, and digital marketing knowledge often hinder progress. Social support from online communities helps housewives overcome these challenges and expand business opportunities. The study concludes that social media plays a crucial role in the economic and social empowerment of housewives, providing psychological benefits such as increased self-confidence and skill development.